Hubungan Pola Makan Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Nanggeleng Kota Sukabumi - Ikkeu Nuraeni; Dhinny Novryanthi; Saepul Mustopa (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Background: Anemia is a health problem that is often experienced by pregnant women due to poor eating patterns during pregnancy. Objective: This study aims to determine the relationship between diet and the incidence of anemia in pregnant women in the working area of the Nanggeleng Community Health Center, Sukabumi City. Method: The type of research used was correlational with 51 samples selected through cluster random sampling. Result: The results of the study showed that the majority of respondents' eating patterns were poor, namely 27 (52.9%) respondents and a small portion of respondents' eating patterns were good, namely 10 (19), 6%) respondents. In the majority of cases, paleness in respondents was due to iron deficiency, namely 27 (52.9%) respondents and a small percentage of cases of anemia in respondents were non-frail, namely 24 (47.1%) respondents. It can be seen that the consequences of the measurable test using Chi-Square can be obtained by P-Value = 0.000, meaning < 0.05. Rejected by Ho, who stated that there was a relationship between dietary patterns and the incidence of anemia in pregnant women in the Health Center Work Area. This was based on rejecting the hypothesis. Based on the results and discussions regarding the relationship between diet and morbidity rates. Conclusion: It can be concluded that the research results show that the description of examples of eating patterns at the level of anemia in pregnant women in the working area of the Nanggeleng Community Health Center, Sukabumi City, most of them have unhealthy eating patterns. The results of the research show that there is a relationship between diet and the incidence of anemia in pregnant women in the working area of the Nenggeleng Community Health Center, Sukabumi City.